One-Year Results of a Multicenter Study: Intraocular Pressure–Lowering Effect of Combined Phacoemulsification, Goniosynechialysis, and Goniotomy for Cases of Advanced Primary Angle-Closure Glaucoma With Cataract. Issue 6 (23rd November 2022) - Song, Yunhe; Zhang, Yi; Li, Fei; Zhang, Yingzhe; Lin, Fengbin; Lv, Aiguo; Li, Xiaoyan; Lu, Ping; Xiao, Meichun; Zhang, Hengli; Yan, Xiaowei; Zhu, Xiaomin; et al.
Abstract : Purpose: To evaluate the intraocular pressure (IOP)-lowering effect of the combination of phacoemulsification with intraocular lens implantation (PEI), goniosynechialysis (GSL), and goniotomy (GT) in eyes of advanced primary angle-closure glaucoma (PACG) with cataract. Design: Multicenter observational study. Methods: We enrolled 83 eyes of 83 patients with advanced PACG who received combined PEI+GSL+GT at 8 ophthalmic institutes. Each patient was assessed before treatment and at 1, 7 days, 1, 3, 6, and 12 months postsurgery. The criteria for complete success were IOP within 6 to 18 mm Hg and at least 20% of reduction in IOP from baseline without ocular hypotensive medications or reoperation. The definition of qualified success was similar to that of complete success, except for the need for ocular hypotensive medications. The potential prognostic factors for surgical success were investigated using a multivariate logistic model. Results: All participants completed 1 year of follow-up. Complete and qualified success were achieved in 74 (89.1%) and 79 (95.2%) of 83 eyes, respectively. The mean preoperative and postsurgical IOPs were 27.4±7.3 and 14.2±2.6 mm Hg, respectively. Participants used an average of 2.0 and 0.3 types of ocular hypotensive medications before and after surgery, respectively. The chief complications included hyphema (n=9), IOP spike (n=9), and corneal edema (n=8). None of the eyes required reoperation or developed vision-threatening complications. Multivariate analysis showed that older age was associated with a higher probability of complete success (odds ratio=1.13; 95% CI: 1.02–1.25; P =0.020). Conclusions: The 1-year results of combination of PEI+GSL+GT in treating advanced PACG cases with cataract appear to be safe and effective. Further large-scale multination and multicenter studies are warranted.